Research on Influence of Impact of Microparticles and Sewing Needles on Destruction of Solid Bodies - KHRISTOFOROV, B. D. (Engineering Transactions, 2010)
Impact of powders and sewing needles accelerated by explosion on various obstacles has been studied. Formation of channels up to 100 particle diameters in length has been observed when corundum and tungsten powders impacts on steel and duralumin at speeds up to 2 km/s. A mechanism of such super deep penetration of powder jets into metals has been proposed. The possibility of destroying by needles such objects as plexiglass blocks, antimeteorite screens, containers with elastic and explosive materials with a released energy exceeding the energy of needles has been shown. At impact speeds up to 400 m/s the depth of needles penetration into metals is 3–5 times higher than the one calculated for pointed rods at plastic work. The obtained results can be useful for modeling of impact of meteorites, space scraps and technological wasteson space aircrafts and their components.